2023
DOI: 10.1152/ajpheart.00618.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sinus node dysfunction: current understanding and future directions

Abstract: The sinoatrial node (SAN) is the primary pacemaker of the heart. Normal SAN function is crucial in maintaining proper cardiac rhythm and contraction. Sinus node dysfunction (SND) is due to abnormalities within the SAN which can affect the heartbeat frequency, regularity, and the propagation of electrical pulses through the cardiac conduction system. As a result, SND often increases the risk of cardiac arrhythmias. SND is most commonly seen as a disease of the elderly given the role of degenerative fibrosis as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 218 publications
0
12
0
Order By: Relevance
“…In addition, studies have shown that the increase of pyruvate kinase M2 (PKM2) protein expression in PAH can promote the phosphorylation of ERK1/2 and further upregulate the expression of key glycolytic enzymes LDHA and GLUT1, thereby participating in vascular remodeling in PAH. However, increasing shikonin decreased the protein level of PKM2, decreased the phosphorylation level of ERK1/2 and the expression level of GLUT1 protein, and inhibited the progression of PAH (Li et al, 2023). A hypoxia-induced adaptive response is initiated by HIF-1, which increases or represses the expression of genes regulating vascular tone, autophagic response, cell metabolism, and proliferation.…”
Section: Glycolysis and Glucose Oxidation In Pahmentioning
confidence: 99%
“…In addition, studies have shown that the increase of pyruvate kinase M2 (PKM2) protein expression in PAH can promote the phosphorylation of ERK1/2 and further upregulate the expression of key glycolytic enzymes LDHA and GLUT1, thereby participating in vascular remodeling in PAH. However, increasing shikonin decreased the protein level of PKM2, decreased the phosphorylation level of ERK1/2 and the expression level of GLUT1 protein, and inhibited the progression of PAH (Li et al, 2023). A hypoxia-induced adaptive response is initiated by HIF-1, which increases or represses the expression of genes regulating vascular tone, autophagic response, cell metabolism, and proliferation.…”
Section: Glycolysis and Glucose Oxidation In Pahmentioning
confidence: 99%
“…The relationship between symptoms and emotional or psychological distress, physical activity, positional changes, medical measures, and typical triggers (cough, prolonged upright posture, urination, and defecation) should be explored along with pulse rate change, if measured during an episode ( Kusumoto et al, 2019 ). In addition, family history provides data on irreversible genetic abnormalities, including familial SND, inherited cardiomyopathies, or inheritable arrhythmic conditions associated with SND (catecholaminergic polymorphic ventricular tachycardia and long QT syndrome) that are often attributed to gene mutation ( Manoj et al, 2022 ). Physical examination and a detailed history help exclude systemic diseases, drug effects, and surgical trauma.…”
Section: Selection Criteria For Patients Undergoing Cardioneuroablati...mentioning
confidence: 99%
“…Observing the heart rate response through pharmacologic interventions is not frequently warranted in clinical practice, but the evaluation of the intrinsic heart rate might be helpful if there is a question regarding intrinsic versus extrinsic SND. As an anticholinergic agent, atropine can simulate the effect of vagal denervation, manifesting an acceleration of both spontaneous depolarization of sinoatrial node pacemaker cells and atrioventricular conduction, which increases heart rate ( Manoj et al, 2022 ). Thus, dysfunction of the sinus node in a patient with bradyarrhythmia, which might be attributed to vagal overactivity, could restore partly or completely when vagal neural control was largely eliminated using atropine.…”
Section: Selection Criteria For Patients Undergoing Cardioneuroablati...mentioning
confidence: 99%
“…The pacing cells synchronize to generate an impulse of sufficient strength to propagate through sinoatrial conduction pathways to excite the atrial myocardium 3,4 . Additionally, the sinus node and conduction pathways contain fibrous tissue 5 and connexin 45 2,6 and no connexin 43 7 resulting in low conductance. The slowed conduction from the sinus node to the atria permits charge to build and overcome the source‐sink difficulty 2,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the sinus node and conduction pathways contain fibrous tissue 5 and connexin 45 2,6 and no connexin 43 7 resulting in low conductance. The slowed conduction from the sinus node to the atria permits charge to build and overcome the source‐sink difficulty 2,8 . However, these features that assure enough current to overcome the source‐sink challenge are also those that are vulnerable to alterations that slow impulse propagation leading to sinus node dysfunction (Figure 1).…”
Section: Introductionmentioning
confidence: 99%